1994
DOI: 10.1007/bf00013069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stitched laminated ENF specimens for interlaminar mode II fracture toughness

Abstract: Two simple micromechanics based models are proposed to predict the effect of through-thickness reinforcement (stitching) on the improvement of delamination crack growth resistance in end-notched flexure (ENF) specimens. In the first model, it is assumed that stitches stretch elastically and then rupture when the load carried approaches the failure load. In the second model, it is assumed that stitches are discontinuous and that the stitch thread-matrix interface is completely frictional. Approximate closed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Eq. (2) is the same as to that proposed by Jain and Mai (1994b) for a discontinuous or independent stitch. However, it should be emphasized that there is only one z-rod at each z-reinforcement location in the present model whereas there are two stitch threads at each stitch reinforcement entity.…”
Section: Axial Force-displacement Relationshipmentioning
confidence: 61%
“…Eq. (2) is the same as to that proposed by Jain and Mai (1994b) for a discontinuous or independent stitch. However, it should be emphasized that there is only one z-rod at each z-reinforcement location in the present model whereas there are two stitch threads at each stitch reinforcement entity.…”
Section: Axial Force-displacement Relationshipmentioning
confidence: 61%
“…Given the critical potential energy release rate of the composite laminate for mode II fracture, G IIC , the shear stress ahead of the crack-tip at any location r can be obtained from Eq. (8). Here, the critical energy release rate, G IIC , is considered a material constant.…”
Section: The Critical Shear Stress Criterionmentioning
confidence: 99%
“…Jain and Mai [8,9] have also studied mode II fracture toughness of stitched laminated EndNotched-Flexure (ENF) specimens by using first-order shear deformation laminated plate theory and beam theory. In the case of stitching, the bridging force comes from the elastic stretching of the threads.…”
Section: Introductionmentioning
confidence: 99%
“…In 1990s, Mai et al [6][7][8][9][10] Mouritz and Cox [11] proposed an approach to evaluate the properties of the stitched laminates. These studies showed that the load-carrying capacity of the laminates can be improved through a proper stitching reinforcement.…”
Section: Introductionmentioning
confidence: 99%